Phenotypic characteristics of native chickens in Libya based on morphometric and plumage traits - HASAN MOFTAH AHMED AHMAD; MUHAMMAD RIZWAN YOUSAF; BILAL AHMED; EDY KURNIANTO; DELA AYU LESTARI; FATMAWATI MUSTOFA; SUTOPO SUTOPO; ASEP SETIAJI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ahmad HMA, Yousaf MR, Ahmed B, Kurnianto E, Lestari DA, Mustofa F, Sutopo S, Setiaji A, 2025. Phenotypic characteristics of native chickens in Libya based on morphometric and plumage traits. Biodiversitas 26: 3659-3673. Native Libyan chickens are a widely distributed poultry variety, while undisturbed types often lack distinctive characteristics. This study aimed to analyze phenotypic variations among Indigenous chickens across different regions of Libya using a qualitative approach. This study used a purposive sampling technique. A total of 200 chickens were sampled from Sirte, Abu Hadi, and Abongim. Data analysis using descriptive statistics, boxplot, Shannon Index, Coefficient of Variation (CV), Principal Component Analysis (PCA), ANOVA test and correlation test. The findings revealed that there were differences in the variation of phenotypic characteristics, indicating that genetic factors play a major role in shaping these traits. The most common feather color was black (36.5%). Black with a white side was the most common shank color (45.5%). The most common comb type was the pea comb (54%). Black (45%) and brown-yellow (46.5%) beak colors were most prevalent. Highly significant differences between regions occurred in leg color (p = 0.008) and beak color (p = 0.018), whereas highly significant differences between sexes were for all the traits (p<0.05). Good correlations were also found between beak color and comb shape (r = 0.777), and leg color and feather color (r = 0.776). PCA analysis showed that the maximum variation in phenotypes was explained by feather color (79.16%). Environmental influences and local breeding practices contributed to the distribution. Preservation of native phenotypes has substantial conservation value because it provides resilient traits essential for local and regional agriculture and contributes to genetic diversity. Therefore, to enhance the sustainability, selective breeding programs should prioritize the maintenance and enhancement of the most common and adaptive traits.